2012
DOI: 10.1093/scan/nss079
|View full text |Cite
|
Sign up to set email alerts
|

Specific neural correlates of successful learning and adaptation during social exchanges

Abstract: Cooperation and betrayal are universal features of social interactions, and knowing who to trust is vital in human society. Previous studies have identified brain regions engaged by decision making during social encounters, but the mechanisms supporting modification of future behaviour by utilizing social experience are not well characterized. Using functional magnetic resonance imaging (fMRI), we show that cooperation and betrayal during social exchanges elicit specific patterns of neural activity associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…Finally, the current findings also extend the results described by Smith-Collins et al (2013) . These authors investigated how participants make decisions in a trust game where the same and new partners re-appear in consecutive rounds and feedback is given.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, the current findings also extend the results described by Smith-Collins et al (2013) . These authors investigated how participants make decisions in a trust game where the same and new partners re-appear in consecutive rounds and feedback is given.…”
Section: Discussionsupporting
confidence: 91%
“…trusting after unexpected cooperation or distrusting after unexpected betrayal. While Smith-Collins et al (2013) focus on the response towards an identifiable partner when group composition is changing, we show that trust-based learning (with increasing caudate activity over time) can also take place based on expectations of the entire group.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A series of studies using the trust game have suggested that learning about the trustworthiness of others is associated with activity in the brain's reward circuitry that mimics activity seen during learning about (non-social) reward values of objects [47][48][49][50][51][52] . For instance, information about the trustee's moral character 47 or experience with a trustee's behaviour 50 changed both neural activity in the striatum during the outcome phase of each round and subsequent investment behaviour in the game, and these effects changed over the course of the experiment.…”
Section: Learning About Othersmentioning
confidence: 99%
“…Accordingly, we first identified consistent brain activations in the trust stage of the one-shot IG and the multiround IG, and then investigated common and different neural patterns of these stages. Moreover, activations in the AI and striatum have been found not only during the trust stage, but also the reciprocity and feedback stage of the multiround IG, respectively [Baumgartner et al, 2009;Chang et al, 2011;Fareri et al, 2015;King-Casas et al, 2005;Smith-Collins et al, 2013]. Thus, our second aim was to determine whether decisions to reciprocate and feedback learning involve different neural mechanisms.…”
Section: Introductionmentioning
confidence: 99%